Math, asked by poornimapoojary28, 4 months ago

\frac{x^2 + 1 }{x} = 7 , Find : \\1) x+ \frac{1}{x} \\\\ 2) x^3+\frac{1}{x^3}

Answers

Answered by mathdude500
3

\large\underline{\sf{Given- }}

\rm :\longmapsto\: \dfrac{ {x}^{2}  + 1}{x} = 7

\large\underline{\sf{To\:Find - }}

\rm :\longmapsto\:1)  \:  \:  \:  \: \: x + \dfrac{1}{x}

\rm :\longmapsto\:2)  \:  \:  \:  \: \:  {x}^{3}  + \dfrac{1}{ {x}^{3} }

\large\underline{\sf{Solution-}}

Given that

\rm :\longmapsto\: \dfrac{ {x}^{2}  + 1}{x} = 7

\rm :\longmapsto\: \dfrac{ {x}^{2}}{x} +  \dfrac{1}{x}  = 7

\bf\implies \: \:  x+  \: \dfrac{1}{x}  = 7

Now, On cubing both sides, we get

\rm :\longmapsto\: {\bigg(x + \dfrac{1}{x} \bigg) }^{3} =  {7}^{3}

\rm :\longmapsto\: {x}^{3} + \dfrac{1}{ {x}^{3} }  + 3 \times x \times \dfrac{1}{x} \bigg(x + \dfrac{1}{x} \bigg) = 343

 \:  \:  \:  \:  \:  \: \red{\bigg \{ \because \:  {(x + y)}^{3} =  {x}^{3} +  {y}^{3} + 3xy(x + y)   \bigg \}}

\rm :\longmapsto\: {x}^{3} + \dfrac{1}{ {x}^{3} }  + 3  \times 7 = 343

 \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \red{\bigg \{ \because \: x +  \dfrac{1}{x}  = 7\bigg \}}

\rm :\longmapsto\: {x}^{3} + \dfrac{1}{ {x}^{3} }  + 21 = 343

\rm :\longmapsto\: {x}^{3} + \dfrac{1}{ {x}^{3} } = 343 - 21

\bf :\longmapsto\: {x}^{3} + \dfrac{1}{ {x}^{3} } = 322

More Identities to know:

  • (a + b)² = a² + 2ab + b²

  • (a - b)² = a² - 2ab + b²

  • a² - b² = (a + b)(a - b)

  • (a + b)² = (a - b)² + 4ab

  • (a - b)² = (a + b)² - 4ab

  • (a + b)² + (a - b)² = 2(a² + b²)

  • (a + b)³ = a³ + b³ + 3ab(a + b)

  • (a - b)³ = a³ - b³ - 3ab(a - b)
Similar questions